Diversity and community distribution of soil bacterial in the Yellow River irrigation area of Ningxia, China. - Xia Wu; Jinjun Cai; Zhangjun Wang; Weiqian Li; Gang Chen; Yangyang Bai (PLoS ONE, 2024)
The bacterial community performs an essential ecological role in maintaining agriculture systems. The roles of bacteria in the forest, marine, and agricultural systems have been studied extensively and intensively. However, similar studies in the areas irrigated by the Yellow River remain limited. In this study, we used Illumina sequencing analysis with the 16S rRNA method to analyze the bacterial diversity, community structure, and influencing factors in soil samples from eight regions of the Yellow River irrigation area in northwestern China. The bacterial community structure and diversity varied among samples from the eight regions. The samples differed significantly in terms of the bacterial community composition. Proteobacteria (approximately 12.4%-55.7%) accounted for the largest proportion and was the dominant bacteria, followed by Actinobacteria (approximately 9.2%-39.7%), Bacteroidetes (approximately 1.8%-21.5%), and Chloroflexi (approximately 2.7%-12.6%). Among the physicochemical variables, the soil pH in the eight regions was mildly alkaline, and the total nitrogen, total phosphorus, and total potassium contents in the soils differed significantly. However, the trend in the variations of the above variables was essentially similar. Soil bacteria in Yongning county had greater Chao1, Shannon-Wiener, and Simpson indices than those in the other regions. Notably, soil moisture, organic matter, and total nitrogen were recognized as the primary factors influencing the bacterial community in the Yellow River irrigation area. Our results revealed the laws of variation in soil bacterial diversity and community composition in the Yellow River irrigation area. Our findings could be beneficial for maintaining sustainable ecological practices in the Yellow River irrigation area.